Penerapan Evaluasi CIPP (Context, Input, Process,Product) Dalam Program Rintisan Madrasah Unggul Di MTsN 1 Yogyakarta - Dicky Artanto; Hasan Ibadin; Suwadi (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2023)
Evaluation is an important activity to carry out because it is a starting point to determine the decisions and policies that will be taken as a determinant of the direction of the course of a program. This article examines the application of CIPP (Context, Input, Process, and Product) evaluation in the superior madrasah pilot program at MTsN 1 Yogyakarta. This research method uses field research, namely field research at MTsN 1 Yogyakarta by interviewing several respondents, field observations, and documentation analysis using data in the form of documents and related data sources contained in MTsN 1 Yogyakarta. Data analysis using the Miles and Huberman method is by collecting data, reducing data, presenting data, and drawing conclusions or verifying data. Based on the results of research that the superior madrasah pilot program at MTsN 1 Yogyakarta can be considered to have been carried out in accordance with the intended purpose of the program, this is evidenced by the achievements achieved by students who are members of a special superior class that they have been able to make a work product that is in the form of goods such as electric masks, non-chemical handsanitizers,  also in terms of scientific papers contested at the provincial and national levels. Although it has been considered successfully realized, there are several things that must be improved and improved, namely related to the human resources of educators who must be trained to be qualified in the field of scientific research.